Open Source ERP for SME - . Tristiyanto (Bandar Lampung University (UBL), 2012)
There are huge barriers for small medium enterprises (SME) to adopt enterprises resource planning (ERP) into their systems. Open source ERP is one of the solutions to overcome it. This paper describes the reason of SME to apply open source ERP, examines seven open source ERPs, and highlight critical success factors for implementing open source ERP in SME.